Profil kemampuan koneksi matematis siswa dalam materi lingkaran ditinjau dari gaya kognitif field independent dan field dependent - Budiyarti, Danny; Dwijayanti, Ida; Pramasdyahsari, Agnita Siska (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This study aims to determine the profile of students' mathematical connection abilities in circle material in terms of field independent and field dependent cognitive styles. This type of research is a descriptive qualitative research. The research subjects taken were students of junior high school class IX totaling 4 students who had received circle material that had field independent and field dependent cognitive styles. Data collection is done by using GEFT (Group Embeded Figure Test), connection ability test, and interviews. The data analysis technique was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The validity of the data uses source triangulation, namely by comparing data or information from different sources or subjects. The results of this study are students with the FI cognitive style fulfill all indicators of mathematical connection ability, namely (1) finding and understanding the relationship of representations of various concepts and procedures; (2) looking for connections from one procedure to another in an equivalent representation; (3) using mathematics in other fields of study; (4) using connections between mathematical topics; and (5) understanding the equivalent representation of the same concept or procedure. Students with FD cognitive style meet the indicators of mathematical connection ability, namely indicators (1), (3), and (4).